STRATEGI PENINGKATAN KREATIVITAS ANAK MELALUI PENDEKATAN PEMBELAJARAN QUANTUM GAMES DI RAUDHATUL ATHFAL IBNU SINA PALEMBANG - Sartika, Dewi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2019)
Creativity is the ability to create new ones and can be applied in problem solving. Strategies in developing children's creativity need to review four aspects of creativity, namely